A formal approach to the assessment and improvement of terminological models used in information systems engineering. - Wendorff, Peter (Software engineering notes.)
In the design and implementation of any information system identifiers are used to designate concepts. Typical examples are names of classes, variables, modules, database fields, etc. A terminological model is a set of identifiers together with a set of abstractions and a set of links between identifiers and abstractions. Naturally, terminological models embody important knowledge of a system, and therefore they play an important role during the development of information systems. In this paper we propose a metamodel for terminological models that is based on category theory as conceptual and notational framework.